Role of sclerostin in bone and cartilage and its potential as a therapeutic target in bone diseases - Lewiecki, E. Michael (SAGE Publications, 2014)
Sclerostin is a small protein expressed by the SOST gene in osteocytes, bone cells that respond to mechanical stress applied to the skeleton and appear to play an important role in the regulation of bone remodeling. When sclerostin binds to its receptors on the cell surface of osteoblasts, a downstream cascade of intracellular signaling is initiated, with the ultimate effect of inhibiting osteoblastic bone formation. Recent studies have shown that the SOST gene is also expressed by articular chondrocytes and that modulation of its activity may have effects on articular cartilage and subchondral bone. The role of sclerostin in the pathogenesis of osteoarthritis in humans has not yet been defined, and the potential utility of treating osteoarthritis with interventions that alter sclerostin is not known. Rare genetic skeletal disorders in humans with low sclerostin levels, such as sclerosteosis and van Buchem disease, have been associated with a high bone mineral density (BMD) phenotype and low risk of fractures. This has led to the concept that antisclerostin interventions might be useful in the treatment of patients with osteoporosis and skeletal disorders associated with low bone mass. Compounds that inhibit sclerostin have been shown to stimulate bone formation and reduce bone resorption, with a robust increase in BMD. Investigational monoclonal antibodies to sclerostin, including romosozumab, blosozumab, and BPS804, have advanced to phase II clinical trials or beyond. If antisclerostin therapy is found to have beneficial effects on clinical endpoints, such as reduction of fracture risk or improvement in quality of life in patients with osteoarthritis, with a favorable balance of benefit and risk, then this class of compounds may become a prominent addition to the options for therapy of osteoporosis and other skeletal disorders.